Islamic Law Perspective: The Issue of Interfaith Marriage and its Impact on Society in Indonesia - Amin, Ade Ulfa; Syam, Syafruddin; Yazid, Imam (Journal of World Science, 2023)
Indonesia has different cultures, customs, and religions, as well as different beliefs; of course, each society has different rules, including marriage. Every marriage cannot be separated from the important influence of religion, belief, and culture of the community and religious leaders in the area where the community is located. The aim of this research is to explore knowledge about the perspective of Islamic religious law in interfaith marriages. This research also aims to determine the possible social impacts that can occur for those who enter into interfaith marriages in Indonesia. The research method used in this research is a normative legal research method, namely using legal material sources in the form of statutory regulations, court decisions/decisions, contracts/agreements/agreements, legal theory, and expert opinions. The results of the research obtained are that there are no loopholes, and potential interfaith marriages can be legalized according to religious law and law in Indonesia, apart from that, interfaith marriages can trigger potential conflicts between communities, family relationships, husband and wife relationships as well as the resulting negative impact on the resulting children, from interfaith marriages. This research has implications for comparisons of how other Muslim-majority countries handle interfaith marriages within the framework of Islamic law. This can provide valuable insight into alternative approaches and potential best practices for Indonesia.